Niveles de metales en partículas atmosféricas en la zona minera de carbón, norte de Colombia (2017)
Given the importance of the health effects of inhalable particles PM10 and metals associated with them , the levels were evaluated some metals (Al, Cr, V, Hg , Pb, Ni, Zn , Cr , As , Se, cd , Cu , Fe and Co) generated mainly by coal mining activities in the area of La Guajira , northern Colombia. All samples were subjected to a process of acid digestion and analyzed by mass spectrometry source inductively coupled plasma and the atomic absorption technique coupled with cold steam for the case of Hg. With the exception of Hg, all metals analyzed showed statistically significant differences between sampling areas. The vast majority of the metals are present in higher concentrations in the mining area, compared with the site taken as a witness located in the city of Riohacha, at a distance of 150 Km. Moreover, for the overall period metals present in higher concentrations in the dry season than in the rainy. Pb, V and Hg do not exceed the air quality standard set for Colombia, but meanwhile the Ace exceeds the permissible limit of OMS in areas throughout the sampling period. Further statistical analysis confirmed the mining activity as the main source of emission of this type of metal contaminants in the atmosphere over the region of La Guajira.